2022
DOI: 10.3389/fonc.2022.896301
|View full text |Cite
|
Sign up to set email alerts
|

Radium-223 as an Additional Therapeutic Strategy in Highly Selected Patients With Metastatic Breast Cancer: A Case Report

Abstract: Radium-223 is commonly used in metastatic prostate cancer, targeting specifically bone metastases. The use of radium-223 remains, however, poorly evaluated in metastatic breast cancer. We report a case of radium-223 treatment in a 59-year-old patient with bone-only metastatic disease that progressed on multiple lines of systemic treatments. Radium-223 was very well tolerated and resulted in a regression of activity of bone metastases and in a 6-month progression-free survival. However, progression occurred in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the CARBON study of radium-223 in combination with capecitabine, similar results were reported, with no substantial benefit from the combination over capecitabine alone observed [ 17 ]. However, case reports indicate that radium-223 may have efficacy in patients with bone-only metastases [ 18 ], and most patients with prostate cancer have bone-only or bone-dominant metastases. Overall outcome in most solid tumors other than prostate cancer is usually driven by visceral disease, not by bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the CARBON study of radium-223 in combination with capecitabine, similar results were reported, with no substantial benefit from the combination over capecitabine alone observed [ 17 ]. However, case reports indicate that radium-223 may have efficacy in patients with bone-only metastases [ 18 ], and most patients with prostate cancer have bone-only or bone-dominant metastases. Overall outcome in most solid tumors other than prostate cancer is usually driven by visceral disease, not by bone disease.…”
Section: Discussionmentioning
confidence: 99%